(untitled) (Medical Forum Monthly, 2022)
Objective: The present study tries to explore the impact of health anxiety on cyberchondria and mediating effects of metacognitive beliefs. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Bahauddin Zakariya University Multan from September 2021 to January 2022. Materials and Methods: A sample of 320 normal healthy participants of both genders were selected through a pre-determined criteria comprising of (n=163) male, 59.1% and (n=157) were females, 49.1%. A cross-sectional research design was proposed and purposive sampling technique was employed to collect data. The survey consisted of three highly reliable scales measuring the variables in construct (Health Anxiety Inventory, Cyberchondria Severity Scale and Metacognitions Questionnaire–Health Anxiety). The data was analyzed via Smart PLS 3 and SPSS. Using structural equation modeling. Results: The findings revealed that health anxiety is a significant predictor of cyberchondria as (β=0.56, p<0.001, R2 = 0.32) and metacognitive beliefs significantly mediates the association between health anxiety and cyberchondria. The indirect effect between health anxiety and metacognitive beliefs is significant (β=0.59, p<0.001, R2 = 0.35) and indirect effect between metacognitive beliefs and cyberchondria is also significant (β=0.43, p<0.001, R2 = 0.43). Conclusion: The present study observed significant association between health anxiety, metacognitions and cyberchondria. It will help medical practitioners to understand how metacognitive beliefs and health anxiety can cause an increase in cyberchondria in order to design better treatment plans.